The shortage of veterinarians in emergency practice: A survey and analysis. Issue 3 (30th December 2020) - Booth, Matthew; Rishniw, Mark; Kogan, Lori R.
Abstract: Objective: To examine factors that impact veterinarians' decisions to pursue a career in, or remain working in emergency medicine. Design: Survey. Setting: General practitioner and student members of Veterinary Information Network. Animals: None. Interventions: None. Measurement and main results: Veterinarians working in (or having worked in), and students hoping to work in emergency medicine mostly enjoy this type of medicine but find the scheduling and stress of the job create impediments to remaining in the field. Fear of being left without support, especially early in their career, also hinder veterinarians from pursuing a career in or remaining in emergency medicine. Conclusions: Programs that increase flexibility of work hours or schedules, and provide either a formal or informal mentoring environment, might help increase retention of veterinarians within the field and encourage students to consider a career in emergency medicine.